Broken mirrors : the "dowry problem" in India - Wyatt, Robin (SAGE, 2010)
In fairytales, good triumphs over evil and mirrors don't lie. Reality, however, presents a different picture as fairytale marriages fall apart and end in a ghastly nightmare: battered brides, unnatural deaths and the ubiquitous 'dowry'. Why does the spectre of 'dowry death' continue to haunt Indian society even a decade into the 21st century? Robin Wyatt, with Nazia Masood, investigates this very problem in Broken Mirrors, urging readers to look beyond the obvious. The narrative, as it effortlessly turns its gaze from the story of a survivor of domestic violence to that of one accused of the crime, smashes the conventional image of so-called 'dowry deaths'. It picks up each of the shattered pieces of the mirror and looks into them closely, and what emerges is a complex portrait of a society where marriage counselling remains taboo and inaccessible to large sections of the population, where the quest for 'justice', armed with powerful, 'pro-women' anti-dowry laws, brushes aside the truth behind the breakdown of many a perfect marriage.